Factors of Influence of Ore and Rocks on the Dump Truck Body Under Quarry Conditions - Gaffarov Azamat Alisherovich (Scientific Trends, 2025)
In this scientific work, structural, technological, and operational solutions aimed at increasing the service life of dump truck bodies operating under quarry conditions were systematically studied. It was established that the high abrasiveness of quarry rocks, the intensity of load impact, humidity, and corrosion factors cause rapid wear of the body metal, and the mechanisms of action of these processes were analyzed. In the study, structural weak zones were identified by optimizing the body geometry, increasing the strength of welds, reducing stress concentrations, and conducting stress-strain analysis in the ANSYS program.
Keywords: Quarry dump truck, body, life, wear, abrasive impact, hard rocks, hardwall, composite coating, lining, construction steel, body geometry, stress analysis, ANSYS, impact loads, torsion, corrosion.